The allscale framework architecture - Jordan, Herbert; Gschwandtner, Philipp; Thoman, Peter; Zangerl, Peter; Hirsch, Alexander; Fahringer, Thomas; Heller, Thomas; Fey, Dietmar (Parallel Computing, 2020)
The tremendous challenge of developing applications efficiently utilizing the hardware provided by contemporary parallel systems of all scales is among the most limiting factors for the continuous growth of high performance computing. In this article, we present a novel architecture taking on this challenge by providing an infrastructure for the effective development of such applications. Our design combines the expressive power of modern C++, advanced compiler technology, and sophisticated runtime system solutions, with the goal of providing a clean separation of domain specific algorithms, resource management activities, and low-level hardware interactions — all required to be accounted for by high performance applications. The article covers the architecture design, its key aspects, and a first evaluation of the achievable performance of an application implemented based on the proposed infrastructure.
CRIS-Team Scopus Importer:2020-06-23
Keywords: Development efficiency; Efficient computing; Extreme scale; High performance computing; Parallel computing; Parallel runtimes; Productivity; Programming models; Runtimes; Space weather simulation